IMPROVING THE EIGHT GRADE STUDENTS’ COMPETENCE IN USING QUESTION TAGS THROUGH DISCUSSION METHOD AT SMP DELI MURNI MEDAN - Wea, Yolenta; Lumban Raja, Viator; Sembiring, Novalina (Kairos English Language Teaching Journal, 2020)
This research is conducted in order to improve the eight grade studentsâ€™ competence in using question tag through Discussion Method at SMP Deli Murni Medan. It also helps the English teacher of the eight grade students of SMP Deli Murni Medan to manage learning and teaching activities in the classroom. In conducting this research, the writer used Classroom Action Research (CAR) as the method of research. Thisresearch consists of two cycles and each cycle consists of four steps, they were planning, action, observation and reflecting. The data were in the form of qualitative and quantitative data. The qualitative data analyzed the learning process. The quantitative data counted the studentsâ€™ score in pre-test and post-test. The result of this research shows that in teaching question tags through Discssion Method at the eight grade students of SMP Deli Murni Medan could improve their competence in using question tags. Moreever, the studentsâ€™ achievements in pre-test and post-test showed a significant improvement. The total score of quantitative data in pre-test was 1998 with the mean score 54, while the total score in formative test was 2630 with the mean score 71,08Â and the total score of post-test was 3004 with the mean score 81,18. From the result, the writer concluded that Discussion Method could improve studentsâ€™ competence in using question tags.